Patient, staffing and health centre factors associated with annual testing for sexually transmissible infections in remote primary health centres - Hengel, B.; Wand, H.; Ward, J.; Rumbold, A.; Garton, L.; Taylor-Thomson, D.; Silver, B.; McGregor, S.; Dyda, A.; Mein, J.; Knox, J.; Maher, L.; et al. (C S I R O Publishing, 2017)
Background: In high-incidence Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) settings, annual re-testing is an important public health strategy. Using baseline laboratory data (2009–10) from a cluster randomised trial in 67 remote Aboriginal communities, the extent of re-testing was determined, along with the associated patient, staffing and health centre factors. Methods: Annual testing was defined as re-testing in 9–15 months (guideline recommendation) and a broader time period of 5–15 months following an initial negative CT/NG test. Random effects logistic regression was used to determine factors associated with re-testing. Results: Of 10 559 individuals aged ≥16 years with an initial negative CT/NG test (median age = 25 years), 20.3% had a re-test in 9–15 months (23.6% females vs 15.4% males, P < 0.001) and 35.2% in 5–15 months (40.9% females vs 26.5% males, P < 0.001). Factors independently associated with re-testing in 9–15 months in both males and females were: younger age (16–19, 20–24 years); and attending a centre that sees predominantly (>90%) Aboriginal people. Additional factors independently associated with re-testing for females were: being aged 25–29 years, attending a centre that used electronic medical records, and for males, attending a health centre that employed Aboriginal health workers and more male staff. Conclusions: Approximately 20% of people were re-tested within 9–15 months. Re-testing was more common in younger individuals. Findings highlight the importance of recall systems, Aboriginal health workers and male staff to facilitate annual re-testing. Further initiatives may be needed to increase re-testing.